Autophagic flux control in neurodegeneration: Progress and precision targeting—Where do we stand?. (June 2017) - Lumkwana, Dumisile; du Toit, Andre; Kinnear, Craig; Loos, Ben
Graphical abstract: Highlights: Novel methods to assess autophagic flux and discern the dynamics of autophagy in different neuronal types and brain regions. Proposed methods to assess flux so as to discern between molecular defects associated with autophagic cargo and machinery. Understanding of the interplay between flux, autophagosome pool size and aggregate prone protein species. Region specific loss in autophagy proficiency with subsequent protein aggregation and neuronal cell death onset. Autophagy failure in neurodegeneration and autophagy flux control that is aligned with the nature of the molecular defect. Abstract: Neurodegenerative diseases are characterised by the presence of cytoplasmic and nuclear protein aggregates that result in toxicity and neuronal cell death. Autophagy is a physiological cellular process that engulfs primarily long-lived proteins as well as protein aggregates with subsequent cargo delivery for lysosomal degradation. The rate at which the material is degraded through autophagy is referred to as autophagic flux. Although we have progressed substantially in unravelling the role and regulation of the autophagy machinery, its dysfunction in pathology as well as its dynamic changes in the disease progression remains largely unclear. Furthermore, the magnitude of autophagic flux in neuronal subtypes is largely unknown and it is unclear to what extent the flux may be affected in distinct neurodegenerative disease states. In this review, we provide an introduction to autophagy in neuronal homeostasis and indicate how autophagy is currently measured and modulated for therapeutic purposes. We highlight the need not only to develop enhanced methodologies that target and assess autophagic flux precisely, but also to discern the dynamics of autophagy in different neuronal types and brain regions associated with the disease-specific pathology. Finally, we describe how existing and novel techniques for assessing autophagic flux could be implemented in order to distinguish between molecular defects associated with autophagic cargo and the machinery. In doing so, this review may provide novel insights in the assessment and control of autophagic flux that is aligned with the protein clearance dysfunction in neurodegenerative disorders.